“Enlatado de caracol acuático amazónico pomacea maculata <churo> en salmuera - López Vásquez, Rafael (2001)
The present thesis paper, carried out mainly in lquitos City, inside installation of Instituto de Investigaciones de la Amazonía Peruana at National University of the Peruvian Amazonía (Faculties of Food lndustry and Biological Science), and Nauta S.A. Palmetto Plant of Spanish Agency, and with respect to thermal treatment made at Universidad Nacional Agraria - La Malina, determining technological parameters in the manufacture from Amazon Canned Aquatic Snail Pomacea maculata " churo ", with Brine, getting so a sensorial, nutritive product and sanitarily good quality. lt used whole nearly 1200 species, that were collected around near-by areas of lquitos city, who were subjected to trials as: sacrifice type, boiling time, thermal treatment and brine concentration; trying to find most adequate parameters this paper from amazon canned aquatic snail. After experiments carried out did obtain following technological parameters: The sacrifice must realize temperature 90ºC. with concentration 2 %, salt per 5 minutes. The boiling must realize with concentration 2 % salt per 1 O minutes. The pattern sample must contain 2.5% salt. The time and temperature obtained for thermal treatment must be 30.5 minutes to 248° F or 120.1 º C., after product reaches a sterilizing temperature. From point of view sensorial and microbiological, this product is acceptable being possible its industrialization, taking into account best result$ the use this raw material that must be integral, that is, sowing, growth, reproduction, industrialization, distribution and trading, since to get 14.2 % output its use enough profitable.